Smart Mesoporous Silica Nanocarriers for Antitumoral Therapy - Baeza, Alejandro; Vallet-Regí, Maria (Current Topics in Medicinal Chemistry, 2015)
The development of nanocarriers able transport and release therapeutic agents in a controlled manner has provided a promising alternative in the oncology field due to the lack of selectivity of the conventional treatments. The encapsulation of cytotoxic compounds within nanoparticles improves the pharmacokinetic profile of the trapped drugs and allows their selective accumulation into the tumoral tissue owing to the enhance permeation and retention effect (EPR). In addition, the selectivity of the nanocarrier can be enhanced attaching targeting agents on their surface able to be specifically recognized by cancer cells or by the tumor microenvironment. Among the different materials which can be employed, mesoporous silica nanoparticles (MCM-41 type) constitutes a promising candidate due to their very interesting properties such as tuneable size, shape and porosity, high loading capacity, low toxicity, robustness and easiness fabrication and functionalization. This material presents a unique pore architecture which allows the synthesis of stimuliresponsive devices able to release the trapped drugs only in the presence of certain stimuli achieving a precise control on the drug dosage. This review presents some of the recent advances in the development of mesoporous silica nanocarriers for antitumoral therapy paying special attention on the stimuli-responsive systems able to release their load in response to external (light, magnetic field, temperature or ultrasounds) or internal stimulus (enzymes, pH, redox, among others).
Keywords: Drug delivery